The Lisbon Cohort of men who have sex with men - Meireles, P (2015)
Purpose Newly diagnosed HIV infections among men who have sex with men (MSM) are rising in many European countries. Surveillance tools must be tailored to the current state of the epidemic, and include decentralised prospective monitoring of HIV incidence and behavioural changes in key populations. In this scenario, an open prospective cohort study was assembled—The Lisbon Cohort of MSM—aiming to dynamically monitor the frequency of disease and its predictors. Participants The Lisbon Cohort of MSM is an ongoing observational prospective study conducted at a community-based voluntary HIV counselling and testing centre in Lisbon, Portugal (CheckpointLX). Men testing negative for HIV, aged 18 or over and reporting having had sex with men are invited to follow-up visits every 6 months. At each evaluation, a face-to-face interview using a structured questionnaire is conducted, and HIV and syphilis rapid tests are performed by trained peer counsellors. From April 2011 to February 2014, 3106 MSM were eligible to the cohort of whom 923 (29.7%) did not participate. The remaining 2183 (70.3%) MSM were enrolled and 804 had at least one follow-up evaluation, for a total of 893 person-years of observation. Future plans The study findings will be disseminated in peer-reviewed journals and presented at national and international conferences. The follow-up of this cohort of HIV-negative MSM will be a valuable tool for monitoring HIV incidence in a setting where limited prospective information existed. Moreover, it will allow for a deeper analytical approach to the study of population time trends and individual changes in risk factors that currently shape the HIV epidemic among MSM.